Chemical composition and Salmonela occurrence on feedstuffs and protein mixes in rations for swine - Fialho, Elias Tadeu; Sobestiansky, Jurij; Brito, José Renaldi Feitosa; Bellaver, Cláudio; Wentz, Ivo (Pesquisa Agropecuaria Brasileira, 2014)
Samples were collected from 107 farms of breeding herds in the State of Santa Catarina, Brazil, during the period of May 1981 to March 1982. Chemical composition of rations was determined from 859 samples of starter (SR) growing (GWR), finishing (FR), boars (BR), gestation (GR) and lactation (LR) rations, growing-finishing protein mix (GFPM), and also from the feedstuffs yellow corn (C), soybean meal (SM), wheat bran (WB), rice bran (RB), bovine meat and bone meal (MBM) and vitamin-mineral premix (VMP). Salmonella survey was carried out on 379 samples of SR, GWR, FR, GR and LR, protein mix (PM), VMP, MBM and ingredient of vegetable origin. Regarding to chemical composition, no variations were found of the nutrient levels of SR, GWR, and FR in relation to the values recommended by nutritional requirement tables used in Brazil. However, GR, LR and BR showed higher protein levels than those recommended for these phases. Differences were found between chemical composition of ingredients of the analysed samples and those reported in the literature. In 5.8% of the samples, the presence of salmonella was detected. The higher percentage of positive samples (37.5%) was of MBM. PM also presented high contamination level (15.5%) and SR, GWR, FR and GR/LR had 4.1%, 3.33%, 8.51% and 3.28% of positive samples, respectively.
Keywords: rations proximal analysis; bacteriological contamination